Hollow microparticles as a superior delivery system over solid microparticles for the encapsulation of peptides - Loo, Joachim Say Chye (2019)
Purpose Peptides are gaining significant interests as therapeutic agents due to their high targeting specificity and potency. However, their low bioavailability and short half-lives limit their massive potential as therapeutics. The use of dense, solid particles of biodegradable polymer as a universal carrier for peptides also has its challenges, such as inefficient peptide release and low bioactivity. In this paper, it was established that hollow microparticles (h-MPs) instead of solid microparticles (s-MPs), as peptide carriers, could improve the release efficiency, while better preserving their bioactivity. Methods Glucagon like Peptide-1 (GLP-1) was encapsulated as a model peptide. Mass loss, average molecular weight changes, intraparticle pH, polymer-peptide interaction and release studies, together with bioactivity assessment of the peptide for s-MPs and h-MPs were systematically analyzed and evaluated for efficacy. Results The intraparticle pH of s-MPs was as low as 2.64 whereas the pH of h-MPs was 4.99 by day 7. Consequently, 93% of the peptide extracted from h-MPs was still bioactive while only 58% of the peptide extracted from s-MPs was bioactive. Likewise, the cumulative release of GLP-1 by day 14 from h-MPs showed a cumulative amount of 88 ± 8% as compared to 33 ± 6% for s-MPs. Conclusions The cumulative release of peptide can be significantly improved, and the bioactivity can be better preserved by simply using h-MPs instead of s-MPs as carriers